RANCANG BANGUN SMART CONVEYOR PADA UNIT PRODUKSI POLITEKNIK INDUSTRI LOGAM MOROWALI - Setiawan, Angga Tegar; Alfafa, Abduh Malik; Wijayanto, Hendi Lilih; Justiadi, Justiadi; Suwandy, Suwandy (BRILIANT: Jurnal Riset dan Konseptual, 2025)
The metal industry requires an effective quality control system to ensure that produced items meet established standards. This study aims to design a NodeMCU-based smart conveyor capable of automatically sorting metal products based on dimensions while transmitting real-time data on sorted and unsorted product quantities to a MySQL database. This data can be accessed through a website designed to facilitate monitoring. The research methodology includes planning, hardware system design, software development, and system integration stages. NodeMCU serves as the main controller, reading data from dimension-detecting sensors and activating a sorting actuator in the form of a Cylinder Pneumatic. Sorting results are transmitted via Wi-Fi to a database and displayed in real-time on a web interface. The study results demonstrate that the system effectively sorts items based on their dimensions, with the sorting data accessible for real-time monitoring through the website. This implementation enhances production processes, reduces human error, and supports the Industry 4.0 concept through IoT-based data management.